Capture and Concentration of Light to a Spot in Plastic Lightguides by Circular Luminophore Arrangements. Issue 2 (21st November 2014) - Bruijnaers, Bardo J.; Schenning, Albertus P. H. J.; Debije, Michael G.
<x xml:space="preserve">Abstract</x> In this work, it is demonstrated how organic dichroic fluorescent dye molecules embedded in a polymerizable liquid crystal host can be aligned in circular patterns so that sunlight is captured by the fluorophores and the emissions of the dye molecules are all directed primarily towards either a small spot along the edge or towards the center of the plastic lightguide for maximal concentration. By attaching a photovoltaic cell to this spot, the concentrated light can be converted into electricity.